1997
DOI: 10.1002/(sici)1097-0061(19970930)13:12<1167::aid-yea154>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Advancement through Mitosis requires rae1 Gene Function in Fission Yeast

Abstract: Growth of the rae1-1 mutant of Schizosaccharomyces pombe at restrictive temperature results in accumulation of poly(A) + RNA in the nucleus and a cell cycle arrest at the G2/M boundary. We demonstrate here that rae1 function is required for a process other than mRNA export which is essential for advancement through mitosis. Cells lacking rae1 function arrest with elevated Cdc2p kinase levels at a step before the formation of a mitotic spindle and without separation of the spindle pole bodies. Rae1p was localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 34 publications
2
25
1
Order By: Relevance
“…What is the significance of the homology between Rae1 and Bub3? It has been suggested that fission yeast rae1 is involved in the import into the nucleus of proteins required for mitosis (34). Human and Xenopus Mad2, while completely dissimilar in sequence to Bub3, are found along the nuclear envelope in interphase cells and at kinetochores only in mitosis (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…What is the significance of the homology between Rae1 and Bub3? It has been suggested that fission yeast rae1 is involved in the import into the nucleus of proteins required for mitosis (34). Human and Xenopus Mad2, while completely dissimilar in sequence to Bub3, are found along the nuclear envelope in interphase cells and at kinetochores only in mitosis (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Gle2 has recently been proposed to have a mitotic role as a checkpoint protein (50,51). A partial localization to the kinetochore was demonstrated using a FLAG-tagged Gle2 protein (52).…”
Section: Fig 6 Gle2 Bound To Nup98 No Longer Interacts With Tapmentioning
confidence: 99%
“…In other cut21 and cut22 mutant cells, 20S cyclosome appeared to be made, although the level in cut22 mutant might be low. The cut21 gene was isolated, and nucleotide sequence determination indicated that cut21 was identical to rae1 required for RNA export (Brown et al 1995;Whalen et al 1997). cut21-497 mutant cells were arrested at metaphase and the frequency of cut phenotypes was very low.…”
Section: Discussionmentioning
confidence: 99%